Pastor as counselor : wise presence, sacred conversation - Patton, John, 1930- (Nashville, TN : Abingdon Press, 2015)
This very practical book offers no-nonsense instructions for pastors, chaplains, and ministers whose real specialty is the practice of relational wisdom. Patton provides a helpful, step-by-step template for pastoral counseling sessions and clear guidelines for understanding when to defer and how to refer -- all while remaining faithful to the basic pastoral calling to connect persons seeking help with the relationships and resources they need to deal with their lives.
The pastor's specialty: relational wisdom -- The first pastoral counseling conversation -- Continuing the counseling conversation -- Pastoral consultation on family and family-like relationships -- On consulting about family-type problems.
Includes bibliographical references.
Keywords: Pastoral counseling